STRATEGI BAPPERIDA DALAM MENDORONG PENGEMBANGAN INOVASI DAERAH DI KABUPATEN MANDAILING NATAL - Paisal Rahmat; Rahmad Hidayat Lubis; Reza Fansyuri; Juni Khairani; Aida Rahmi; Eli Saharni; Nur Aliyah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to examine Bapperida's strategy in promoting regional innovation in Mandailing Natal Regency. A qualitative approach with a case study design was used. Data collection was conducted through in-depth interviews with key informants, observation of innovation activities, and review of regional planning and policy documents such as the RPJMD and RKPD. The findings indicate that Bapperida plays a crucial role as a policy maker and coordinator in integrating innovation into regional development planning documents. In addition, Bapperida functions as a facilitator that encourages cross-sector collaboration, including with the tourism, health, and fisheries agencies, to expand the application of innovation. The implementation of the strategy is carried out through strengthening coordination, facilitating collaborative forums and capacity-building workshops, assisting regional apparatus, and providing funding support for pilot projects. However, the effectiveness of the strategy still faces obstacles in the form of limited human resources and budget, weak coordination between regional agencies, and a monitoring and evaluation system that is not yet optimal. Therefore, optimization efforts are needed through increasing human resource capacity, developing innovation guidelines and SOPs, integrating innovation into the RKPD, and developing incentive mechanisms and sustainable regional performance evaluations.